Adult children of alcoholics attachment style, coping strategies, relationship quality and life satisfaction. - Cordero, Anne Nicole M.
Four (4) children of alcoholics (2 males; 2 females) aged 18-22 years old from Iloilo City, Negros Occidental, and Miagao were selected through snowball sampling for this study. Three instruments were utilized namely: Revised Parental Drinking Survey (1987), COPE (1997), and an interview guide developed by the researcher. Results showed that majority of the participants were securely attached. Only one was ambivalently attached to her parents. Their main way to cope with stressors was through emotion-focused coping strategies. Furthermore, two participants had a good relationship quality with their parents while the other two had a poor relationship quality. In addition, all of the participants had a high life satisfaction.